Influence of a 6-month physical training program on serum and urinary concentrations of trace metals in middle distance elite runners. Issue 1 (14th November 2019) - Maynar, M.; Bartolomé, I.; Alves, J.; Barrientos, G.; Grijota, F. J.; Robles, M. C.; Muñoz, D.
Abstract: Background: The aim of this survey was to determine the effects of an aerobic physical training program of six months duration on the serum and urinary concentrations of essential trace elements among middle distance runners and untrained, non-sportsmen participants. Methods: 24 well-trained, middle-distance (1500 and 5000 m), aerobic male runners (AG) were recruited at the beginning of their training season and 26 untrained males formed the control group (CG). All participants were from the same region of Spain, and all of them had been living in this area for at least two years. Serum and urine of samples of Cobalt (Co), Copper (Cu), Manganese (Mn), Molybdenum (Mo), Selenium (Se), Vanadium (V) and Zinc (Zn) were obtained at the beginning of the training season, and six months later, from all participants. All samples were analyzed with inductively coupled plasma mass spectrometry (ICP-MS). Results: Two-way ANOVA showed significant differences relative to group effect in serum concentrations of Co, Cu, Mn, Mo, Se and Zn. Attending to time effect, there were differences in Mn ( p  = 0.003) and Zn ( p  = 0.001). The group x time interaction revealed differences only in the case of Mn ( p  = 0.04). In urine, significant differences between group were obtained in Co, Cu, Mn, Se and V. Time effect showed changes in Co, Cy, Mo and Se. Finally, the group and time interaction revealed significant differences in urinary Cu (p = 0.001), Mn ( p  = 0.01) and Se (p = 0.001). Conclusions: A six-month aerobic training program for well-trained athletes induced modifications in the body values of several minerals, a fact which may reflect adaptive responses to physical exercise. The obtained data could be interesting for physicians or coaches in order to consider specific modifications in sportsmen's diets as well as to determine specific nutritional supplementation strategies.